Primary amination and a new method of quantitative assessment for five forming aminated structures - Hieu Ha, Nguyen Thi; Son, Hoang Thai; Moran, Grainne M. (Vietnam Journal of Chemistry, 2014)
The amination of a polymer with a primary amine results in five aminated structures in different proportions: secondary ammonium, secondary amine, cross-linked tertiary ammonium, cross-linked tertiary amine and cross-linked quaternary ammonium. A new quantitative assessment method has been designed and applied for evaluation the five respective individual aminated mole fractions. The method based on a computer program named “Min SS” written in Java script which provides the best match of a set of the five individual aminated mole fractions with the experimental determined element weight fractions of four elements C, H, N and Cl constructing the aminated polymer. This is the only method being able to quantitatively analyse the polyvinylbenzylchloride aminated with primary ethylamine in details, because this crosslinked polymer is insoluble for a convenient analysis. Keywords: “Min SS”, aminated mole fraction, element weight fraction